"Am I a Jew?": Soviet Jewish Youth and Antisemitism on the Home Front during the Second World War. (17th November 2020) - Belsky, Natalie
Abstract: In the wake of the Nazi invasion of June 1941, over one million Soviet Jews were resettled in Central Asia, Siberia, and the Volga and Ural regions for the duration of the war. Prewar antisemitic prejudices and stereotypes, as well as increasingly difficult living conditions, fueled further anti-Jewish sentiment. Children and teenagers were particularly susceptible to harassment because of their frequent contact with local youths at school or in the streets. Often unprepared to deal with these negative attitudes, their responses to and internalization of these early experiences with antisemitism constituted a critical, transformative moment, prompting them to grapple with the meaning of their Jewish identity within the Soviet context.